Lemmas for a Theory of Approximate Optimal Growth - von Weizsacker, C. C. (Review of Economic Studies, 1967)
Journal Article Lemmas for a Theory of Approximate Optimal Growth Get access C. C. von Weizsäcker C. C. von Weizsäcker University of Heidelberg Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 34, Issue 1, January 1967, Pages 143–151, https://doi.org/10.2307/2296575 Published: 01 January 1967